ARTEFAK TULANG SITUS GUA BABI (KALIMANTAN SELATAN): VARIASI TIPOLOGIS DAN TEKNOLOGISNYA - Bagyo Prasetyo (Berkala Arkeologi, 1999)
This site was first discovered in 1995 by a team from the Balai Arkeologi Banjarmasin together with the Puslit Arkenas when carrying out an exploratory survey in the Meratus Mountains. Observation of the ground surface in the cave shows an indication of archaeological data that needs further research. Then continuously, the Banjarmasin Archeology Center carried out excavations from 1996 to 1998. Based on this research, it has produced a number of archaeological data in the form of stone tools industry, bone artifacts, jewelry and pottery. Apart from artifactual data, the remains of fauna, mollusk shells and human components were also found.